Correction: Editorial: Optimizing nutrition from the inside out: innovations in digestion, fermentation, and functional food processing - Naderi, Nassim (Frontiers in Food Science and Technology, 2025)
Graphical AbstractIllustration titled "Optimizing Nutrition from the Inside Out: Innovations in Digestion, Fermentation, and Functional Food Processing" featuring four sections. Top left: "Valorization of By-Products" with an icon of stacked discs, describing repurposing food waste into nutritional ingredients. Top right: "Digestion and Bioavailability" with a digestive system icon, focusing on enhancing nutrient utilization. Bottom left: "Encapsulation Technologies" with a capsule icon, improving stability and delivery of bioactive compounds. Bottom right: "Microbiota Modulation" with a bacteria icon, influencing gut health through dietary interventions.